(untitled) (International Journal of Sustainable Development & World Policy, 2016)
The transportation issue is one of the thematic priorities which give policy makers great inspiration and demand background. Today’s transport networks are leading the way in sustainable, efficient and safe mobility, increasing access to all regions. Large scale projects, infrastructures, networks, EU Cohesion policy’s nearly 22% fund support were mostly emphasized in this sense. This is also valid for candidate countries for Union. This paper discussed the case of Turkey, i.e. she is a candidate state for European Union, and benefiting from the financial instruments for funding regional development process as European Regional Development Fund, Cohesion Fund, European Social Fund, EU Solidarity Fund, IPA and Turkish Cypriot community, Turkey only benefits from the IPA program. This study was prepared in order to present a review upon the transportation projects within the regional development policy of EU. Today, the available member countries are part of a policy mechanism via being joined the mostly known transport projects as Baltic Sea, Interrag V-A sub projects, and Central Europe integration in transportation manners. Those projects were also analyzed in order to show the inspiration themes for the future and today’s concepts and needs of Turkey to be fulfilled in the regional development politics on transportation issue. The number and budgets of transport themed projects and major projects and Turkish TEN-T and similar IPA supported projects were also evaluated in this study.